Use of colistin and sorbitol for better isolation of Serratia marcescens in clinical samples. - Grasso, G. M. (Cambridge University Press, 1988)
A comparison was made of different culture media and procedures for detection of Serratia marcescens from faecal, pharyngeal and ocular swabs collected from 213 neonates. MacConkey agar and MacConkey agar with sorbitol (1%) and/or colistin (200 i.u./ml) were used both for primary isolation and after enrichment using Mossel Enterobacteriaceae broth with colistin (200 i.u./ml). The use of MacConkey agar supplemented with colistin for primary isolation improved considerably the isolation rate of S. marcescens from faecal swabs but not from pharyngeal swabs; the number of ocular isolations were insufficient to demonstrate differences between procedures. Moreover the enrichment procedures consistently increased the number of S. marcescens isolates especially from pharyngeal and ocular swabs. Use of sorbitol made detection of S. marcescens from clinical specimens easier and time- and cost-efficient.